2019
DOI: 10.1039/c9dt02869b
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic chemistry of calcitermin – the picklock of its antimicrobial activity

Abstract: Formation equilibria of Zn(ii) and Cu(ii) complexes of antimicrobial calcitermin and its mutants are studied; impressive MIC breakpoints are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…Interestingly, previous studies show that the antimicrobial activity of calcitermin is lost at physiological pH. 48 Thus, the present results can suggest that its antimicrobial way of action is related to the metal binding affinities of the competing systems. A slight different behaviour is observed, instead, in the case of Zn( ii ) ions, where calcitermin almost steadily maintains its efficacy as a ligand throughout the explored pH range.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, previous studies show that the antimicrobial activity of calcitermin is lost at physiological pH. 48 Thus, the present results can suggest that its antimicrobial way of action is related to the metal binding affinities of the competing systems. A slight different behaviour is observed, instead, in the case of Zn( ii ) ions, where calcitermin almost steadily maintains its efficacy as a ligand throughout the explored pH range.…”
Section: Resultssupporting
confidence: 53%
“…48 Calcitermin contains three alternated histidines (HXHXH), two lysines, one glutamic acid and free amino- and carboxyl-termini. Furthermore, its antimicrobial activity is enhanced in the presence of Zn( ii ) and Cu( ii ) under acidic conditions, 48 representing a possible natural competitor and antagonist of ZinT in the host human organism. The competition plots of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We compared these two chelating systems (calcitermin and the metal-binding sites of Zrt2) (Figure 6), which may potentially compete for metal acquisition during infections, and according to our thermodynamic results, we observed that calcitermin forms more stable complexes than each binding domain of Zrt2, thus suggesting that it is able to withhold metal micronutrients from the surrounding environment. Such results were also confirmed by the Kd values calculated for Zn 2+ and Cu 2+ complexes with calcitermin at pH 7.4 (3.07•× 10 −7 and 1.31 ו10 −10 , respectively) [31]. As previously mentioned, C. albicans can express two main zinc transporters of the ZIP family: Zrt1 and Zrt2.…”
Section: A Qualitative Evaluation Of Zrt2 Metal-binding Abilitysupporting
confidence: 82%
“…Calcitermin is an antimicrobial peptide found in human airways, which corresponds to the cleavage product of the human protein calgranulin C at the carboxyl-terminus. Its antimicrobial activity is enhanced by acidic pH and by the presence of zinc or copper ions [ 30 , 31 ], thus suggesting a possible role of calcitermin in the nutritional immunity process. Furthermore, calcitermin contains three evolutionarily conserved alternated histidines (HxHxH), which can act as metal binding sites under acidic condition.…”
Section: Resultsmentioning
confidence: 99%
“…The constants (pKa) accompanying the dissociation of another functional group and formation of the CuHL 1 and CuHL 2 species in the general reaction CuH 2 L ↔ CuHL + H + are 6.13 and 5.61, respectively (Table 1). The pKa value of this deprotonation step is much lower than the one detected in the free ligands (6.86 and 6.93, respectively; Table S1) and most likely corresponds to the binding of an imidazole nitrogen to the Cu(II) ion [32]. Therefore, potentiometric data confirm the participation of these moieties in the coordination.…”
Section: Potentiometrymentioning
confidence: 72%